2011
DOI: 10.1039/c0cp02408b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of oxygen evolution at α-Fe2O3 photoanodes: a study by photoelectrochemical impedance spectroscopy

Abstract: Photoelectrochemical Impedance Spectroscopy (PEIS) has been used to characterize the kinetics of electron transfer and recombination taking place during oxygen evolution at illuminated polycrystalline α-Fe(2)O(3) electrodes prepared by aerosol-assisted chemical vapour deposition from a ferrocene precursor. The PEIS results were analysed using a phenomenological approach since the mechanism of the oxygen evolution reaction is not known a priori. The results indicate that the photocurrent onset potential is stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
278
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(303 citation statements)
references
References 34 publications
18
278
1
1
Order By: Relevance
“…Similar looking impedance spectra have recently been reported for hematite electrodes, and a variety of equivalent circuits put forth interpret these spectra. 11,45 In these analyses, the low frequency semicircle is generally attributed to the series arrangement of the depletion capacitance of the semiconductor SC C and the Helmholtz capacitance at the electrode surface, and the role of surface states has largely been ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Similar looking impedance spectra have recently been reported for hematite electrodes, and a variety of equivalent circuits put forth interpret these spectra. 11,45 In these analyses, the low frequency semicircle is generally attributed to the series arrangement of the depletion capacitance of the semiconductor SC C and the Helmholtz capacitance at the electrode surface, and the role of surface states has largely been ignored.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the negligible faradaic, steady state photocurrent densities at these potentials is often attributed to slow hole transfer kinetics of water oxidation. 25,26,[28][29][30] We suggest that this may be an intrinsic part of the bimolecular mechanism of water oxidation on the hematite surface. At high applied potentials, however, the photocurrent density is essentially the same for the H 2 O and [Fe(CN) 6 ] 3-/4-systems; the minor difference is attributed to Fermi level pinning in the H 2 O electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…24 The water oxidation (oxygen evolution) reaction at the hematite electrode surface is generally reported to be sluggish, however, which allows for increased recombination and a concomitant loss in efficiency. [25][26][27][28][29][30] A detailed understanding of the water oxidation reaction at the hematite electrode surface is therefore very important in devising strategies to overcome this kinetic barrier. There have been several recent studies, employing a variety of techniques, to understand the nature of the slow water splitting 4 reaction with hematite photoelectrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main causes of the low performance of hematite is related to the large overpotentials required for water oxidation (around 500 mV), and surface treatments have proven to enhance notably water splitting performances. 10−12 It has been suggested that the reasons for these large overpotentials are related to sluggish hole transfer to the electrolyte 13,14 and to the existence of traps in the bulk and at the semiconductor/ electrolyte interface, 15−17 leading to high recombination. 18,19 Clearly, the separation of the different processes that constitute the oxidative current and the identification of the main kinetic bottlenecks are complex tasks.…”
Section: Irect Transformation Of Solar Energy Into Chemical Energymentioning
confidence: 99%